Analysis and Modeling of UAV Near-ground Communication Channel. (April 2020) - Hao-qi, Bi; Xin, Xiang; Na, Li
Abstract: UAV communication platform has become a reliable solution to meet the needs of users in some unexpected situations. In this paper, the statistical method of small area modeling is used to model the UAV near-ground communication channel. The channel is abstracted into three factors: time-delay power spectrum, Doppler power spectrum and Rice factor. As a result, a new method of channel delay generation is introduced, and the time-varying Doppler frequency gain factor is adopted. The simulation results show that the UAV near-ground communication channel is a Rice channel whose amplitude obeys Rayleigh distribution and phase obeys uniform distribution. The bit-error-rate of UAV near-ground communication channel is much higher than that of AWGN channel. At the same time, the constellation chart also shows that the signal passing through the UAV near-ground communication channel will cause strong inter-symbol crosstalk.